(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This study presents a comparative analysis of villain characters in English and Uzbek folk fairy tales, focusing on their narrative functions, symbolic meanings, and cultural representations. Villains play a crucial role in shaping the moral structure of fairy tales, as they often embody fear, evil, and social warnings while highlighting positive values through contrast. By examining selected English and Uzbek folk tales, this research explores how different cultural, historical, and social contexts influence the portrayal of antagonistic characters. The findings reveal that English fairy tales often depict villains as supernatural beings such as witches, giants, or stepmothers, emphasizing individual greed, jealousy, and ambition.